Dynamic Capabilities and Business Performance of Batik SMEs in Solo City: The Mediating Role of Organizational Resilience and the Moderating Effect of Omnichannel Business Model Innovation - Julius D. Aritonang; Willy Arafah (Green Publisher Indonesia, 2026)
This research aims to analyze the influence of dynamic capabilities on the business performance of batik SMEs in the city of Solo, with organizational resilience as a mediating variable and omnichannel business model innovation as a moderating variable. A quantitative approach was used with a survey method involving 120 batik SMEs. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that dynamic capabilities have a positive and significant effect on organizational resilience, which in turn positively affects business performance. However, dynamic capabilities do not have a direct effect on business performance. These findings indicate that organizational resilience fully mediates the relationship between dynamic capabilities and business performance. In addition, omnichannel business model innovation strengthens the influence of organizational resilience on business performance. These results confirm the importance of strategic capabilities, organizational resilience, and integration of business channels in improving the performance of batik SMEs in a dynamic business environment.